Polarization disorder of decidual NK cells in unexplained recurrent spontaneous abortion revealed by single-cell transcriptome analysis - Dingchen Pan; Qian Liu; Le Du; Yang Yang; Guojing Jiang (BMC, 2022)
Abstract Background Unexplained recurrent spontaneous abortion (URSA) is one of the most common diseases in pregnancy and is mainly caused by immune disorders. The foetus is similar to semiallogeneic maternal tissue, so the balance of immune tolerance must be dynamically maintained during pregnancy. Decidual natural killer (dNK) cells primarily mediate the immune tolerance microenvironment at the maternal-fetal interface. By using single-cell RNA sequencing (scRNA-seq) and high-throughput transcriptome sequencing analysis, we explored the characteristic distribution of dNK cells in URSA patients. Methods Control maternal-fetal interface tissue (from normal pregnant women, n = 3) and case maternal-fetal interface tissue (from patients with URSA, n = 3) samples were analysed by scRNA-seq and high-throughput transcriptome sequencing. Results By scRNA-seq, we demonstrated the maturation process of the transition of dNK cells from cytotoxic characteristics to immune tolerance in transcriptome analysis. Moreover, compared with normal pregnant women, serious disturbances in the polarization process of dNK cells were found in URSA. Simultaneously, the transcriptional level of the extracellular matrix (ECM) in URSA patients showed a significant decrease. The dNK cells interacted with extravillous trophoblasts to achieve immune-tolerant polarization. Conclusions Insufficient expression of KIRs during dNK cell differentiation might be a key reason why polarized dNK cells still had high cytotoxic reactivity in URSA patients. Abnormal expression of ECM may affect the interaction of dNK cells with EVTs, making dNK cells immature. Both resulted in maternal immune intolerance to the foetus during pregnancy.